The effectiveness of the combination of Moringa oleifera extract and propolis on Porphyromonas gingivalis biofilms compared to 0.7% tetracycline - Hansen Kurniawan; W. Widyastuti; Mery Esterlita Hutapea (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: Periodontitis is an inflammatory disease that occurs in periodontal tissues. Porphyromonas gingivalis is also known as a bacterium commonly associated with the pathogenesis of periodontitis. Tetracycline is one of the antibiotics often used in periodontal tissue treatment. Propolis and Moringa oleifera are also known to have certain compounds assumed to be able to inhibit biofilm growth. Purpose: This study aims to understand the effectiveness of the combination of Moringa oleifera and propolis on porphyomonas gingivalis biofilms compared to 0.7% tetracycline. Methods: A biofilm inhibition activity test was performed using the broth micro dilution method. First, bacteria were prepared by making a suspension in brain heart infusion media and adjusting it to 0.5 McFarland I standard. Second, fifteen samples were divided into five groups; group K as control group (0.1% sodium carboxymethyl cellulose), T (0.7% tetracycline), and treatment groups with the combination of propolis and Moringa oleifera in various concentrations, such as P1(10%+20%), P2(10%+40%), and P3(10%+80%). Third, the result data obtained in the form of optical density (OD) was read by using an ELISA reader. Next, statistical analysis using analysis of the variance test was conducted (p<0.05. Results: There was no significant difference between group T and group P1 (0.075). Nevertheless, there were significant differences between group T and group P2 as well as between group T and group P3 (0.00) (p=< 0.05). Conclusion: The combination of 10% propolis and 40% Moringa oleifera as well as the combination of 10% propolis and 80% Moringa oleifera have better antibacterial effectiveness against Porphyromonas gingivalis biofilm than 0.7% tetracycline.